Magnitude and associated factors of diabetes mellitus and hypertension among adult HIV-positive individuals receiving highly active antiretroviral therapy at Jugal Hospital, Harar, Ethiopia - Ataro Z (Dove Medical Press, 2018)
Zerihun Ataro,1 Wondimye Ashenafi,2 Jiregna Fayera,3 Tekabe Abdosh3 1Department of Medical Laboratory Sciences, College of Health and Medical Sciences, Haramaya University, Harar, Ethiopia; 2School of Public Health, College of Health and Medical Sciences, Haramaya University, Harar, Ethiopia; 3School of Medicine, College of Health Sciences, Haramaya University, Harar, Ethiopia Background: People with HIV infection are at increased risk of noncommunicable diseases (NCDs). Diabetes mellitus (DM) and hypertension are recognized as the major NCDs. Except few findings in general population, there is no well-documented evidence on the magnitude of NCDs and associated factors among HIV-positive patients. Purpose: The aim of this study was to determine the magnitude and associated factors of DM and hypertension among adult HIV-positive subjects receiving highly active antiretroviral therapy (HAART) Methods: A hospital-based cross-sectional study was conducted from February to April at Jugal Hospital, Harar, Eastern Ethiopia. Sociodemographic and anthropometric data and blood pressure (BP) were collected by senior clinical nurses. A total of 5 mL of venous blood was collected. Serum glucose and lipid profile were measured using the Autolab 18 clinical chemistry analyzer. Data were analyzed using STATA version 13. Results: A total of 425 HIV-infected individuals taking HAART of age ranging from 18 to 68 years were included. The prevalence of DM and hypertension were 7.1% (95% CI: 4.9–9.9) and 12.7% (95% CI: 9.8–16.2), respectively. Increased blood triglyceride (adjusted odds ratio [AOR] =4.7, 95% CI: 1.7–13.1), high BP (AOR =3.3, 95% CI: 1.1–9.5), and high baseline body mass index (BMI) (AOR =8.7, 95% CI: 2.4–31.8) were significantly associated with DM. In contrast, raised waist–hip ratio (AOR =4.6, 95% CI: 1.6–13.3), raised blood glucose (AOR =3.5, 95% CI: 1.1–11.4), increased total cholesterol (AOR =3.9, 95% CI: 1.3–11.9), high current BMI (AOR =3.8, 95% CI: 1.5–9.6), drinking alcohol (AOR =3.4, 95% CI: 1.5–8.1), CD4 count <500 cell/mL (AOR =2.7, 95% CI: 1.3–5.6), and longer duration of HAART (AOR =2.3, 95% CI: 1.1–5.1) were significantly associated with hypertension. Conclusion: DM and hypertension were frequent among HIV patients on HAART, and they were linked to the well-known risk factors. Therefore, regular screening and monitoring of DM and hypertension before and after the initiation of HAART is of paramount importance. Keywords: diabetes mellitus, hypertension, HIV, HAART, Ethiopia